Acute Suppurative Thyroiditis in an Intravenous Drug User with a Preexisting Goiter. (26th March 2018) - Yegya-Raman, Nikhil; Copeland, Tabitha; Parikh, Payal
Abstract : Acute suppurative thyroiditis (AST) is an uncommon, potentially life-threatening cause of a rapidly enlarging neck mass. It may present similarly to subacute thyroiditis, a relatively benign and self-limiting condition. We report a case of AST in an adult intravenous (IV) drug user with a preexisting goiter who presented with a left forearm abscess that grew methicillin-sensitive Staphylococcus aureus . In this particular case, clinical suspicion for AST was high. As a result, early IV antibiotic therapy was initiated, and this led to rapid clinical improvement furthermore preventing airway compromise. To our knowledge, this is the first case of AST in the literature resulting from likely hematogenous spread in the setting of IV drug use and a preexisting goiter. Overall, this case highlights the importance of assessing risk factors for AST in patients whose presentations may seem more typical of subacute thyroiditis. Such an approach will lead to timely diagnosis and treatment to avoid potentially devastating consequences.